Barriers and facilitators to HIV care engagement: Recommendations from people with HIV in rural Arkansas. Issue 2 (6th October 2022) - Marshall, Sarah Alexandra; Tao, Jun; Horton, Heather K.; Montgomery, Madeline C.; Baloh, Jure; Gu, Mofan; Mabin, Cornelius; Cima, Mike; Nunn, Amy S.; Chan, Philip A.; Zaller, Nickolas D.
Abstract: Purpose: Little is known about factors affecting HIV care engagement and retention among rural people with HIV (PWH) in the South. About half of PWH in Arkansas reside in rural areas. The purpose of this study was to explore factors affecting engagement and retention in HIV care among PWH in rural areas of Arkansas. Methods: We conducted an exploratory qualitative study in 2020 and completed individual interviews (N = 11) with PWH in rural counties in Arkansas. Findings: Content analysis revealed the following themes: (1) Barriers to HIV care included long distances to the nearest HIV clinic and transportation issues along with anticipating and/or experiencing HIV‐related stigma; (2) facilitators of HIV care included having a helpful HIV care provider and Ryan White case manager and a social support network that aided them in prioritizing their own health; (3) participants had the most favorable reactions to Ryan White case management, peer navigators, and telemedicine for HIV treatment/care; and (4) participants demonstrated resilience overcoming various obstacles as they worked toward being healthy mentally and physically while living with HIV. Conclusion: Interventions need to address multilevel factors, including hiring PWH as peer navigators and/or caseworkers and offering HIV care via telemedicine, to improve HIV care engagement and retention among rural populations.